Lockdown [large type] : a novel of suspense - King, Laurie R. (Thorndike Press, a part of Gale, a Cengage Company, 2017)
A year ago, Principal Linda McDonald arrived at Guadalupe Middle School determined to overturn the school's reputation for truancy, gang violence, and neglect. One of her initiatives is Career Day: bringing together children, teachers, and community presenters in a celebration of the future. But some in attendance reject McDonald's bright vision. When a shocking turn of events transforms a day of possibilities into an explosive confrontation, the chain of interactions locks together hidden lives, troubling secrets, and the bravest impulses of the human heart.